Chemical-Induced Oral Squamous Cell Neoplasms in Rodents: An Overview of NTP 2-Year Cancer Studies. (July 2021) - Ibrahim, Ruba; Brix, Amy; Malarkey, David E.; Nyska, Abraham; Asif, Michal; Ramot, Yuval
Oral cancer is the seventh most common malignancy worldwide, and lifestyle factors participate in its development. Rodent studies can help identify substances that contribute to its development and provide information on the early stages of carcinogenicity. The National Toxicology Program (NTP) has conducted more than 500 short-term and 2-year toxicology and carcinogenicity studies in rodents, and some of the tested compounds resulted in oral cancer. Our goal was to review the NTP carcinogenic studies to describe those chemicals that have oral carcinogenic outcome in rodents. For this project, we reviewed the results from all NTP carcinogenicity studies and a board-certified veterinary pathologist reviewed the slides from all neoplasms in the oral cavity that were considered treatment related. We have identified 26 chemicals with an adverse effect in the oral cavity. Fourteen chemicals demonstrated clear evidence of carcinogenicity in the oral cavity. We provide information on the carcinogenic findings in rodents together with a detailed description of the morphologic aspects of the oral cancers and speculate that the carcinogenic effects can be induced by different pathological modes of action. The findings reviewed here provide indicators for potential oral carcinogenesis processes in rodent models, which can be further investigated in future mechanistic studies.